2009
DOI: 10.1021/ac801267s
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Apoptosis Based on the Interaction between Annexin V and Phosphatidylserine

Abstract: The detection of apoptosis based on the interaction between annexin V and phosphatidylserine is presented in this paper. The in vitro experimental results demonstrate that annexin V in polyethylenimine film can maintain its high affinity with phosphatidylserine translocated from the inner to the outer plasma membrane of the apoptotic cells, which may consequently inhibit the redox reaction of [Ru(NH(3))(5)Cl](2+/+) at the annexin V and polyethylenimine comodified pyrolytic graphite electrode. Therefore, if Ca(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 21 publications
2
46
0
Order By: Relevance
“…In the present study it was found that treatment with TGF-β1 (10 and 20 ng/ml) significantly upregulated Bax but downregulated Bcl-2 protein expression in BMSCs. Annexin V is another apoptotic promoter that preferentially binds phosphatidylserine and promotes cell apoptosis (30). The present results demonstrated that Annexin V was markedly upregulated in BMSCs following exposure to 10 and 20 ng/ml TGF-β1 for 24 h.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study it was found that treatment with TGF-β1 (10 and 20 ng/ml) significantly upregulated Bax but downregulated Bcl-2 protein expression in BMSCs. Annexin V is another apoptotic promoter that preferentially binds phosphatidylserine and promotes cell apoptosis (30). The present results demonstrated that Annexin V was markedly upregulated in BMSCs following exposure to 10 and 20 ng/ml TGF-β1 for 24 h.…”
Section: Discussionsupporting
confidence: 55%
“…Estimates of apoptosis rates of H9c2 cells widely make use of FITC-AV/PI double staining analyzed by flow cytometry (Shang et al, 2013). The annexin V assay is sensitive and supplies the possibility of detecting early phases of apoptosis before the loss of cell membrane integrity, and annexin V in polyethylenimine film can hold its high affinity following with phosphatidylserine altered from the inner to the outer cell membrane of the apoptotic cells in in vitro experiments (Vermes et al, 1995;Liu et al, 2009). In this study, the cardiomyocyte protection of HA+GA may be associated with the suppression of the cell apoptosis through the decreased apoptotic rates.…”
Section: Discussionmentioning
confidence: 76%
“…The apoptotic ratio was detected using an Annexin V/PI method (21). Briefly, the cells were treated with various concentrations of SM (0, 5, 10 or 20 µM) for 24 h, trypsinized (Gibco Life Technologies) and resuspended in 100 µl binding buffer, followed by addition of 5 µl Annexin V and PI in each tube.…”
Section: Detection Of Apoptosismentioning
confidence: 99%